E-Learning: Evolution, Implementation, and Impact on Educational Transformation - Syifa Aqilah; Didik Himmawan (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
E-learning has become a significant innovation in education, leveraging information and communication technology to provide flexible learning that transcends time and space. Its evolution has ranged from simple teaching machines in the 19th century to today's sophisticated digital platforms, supported by advances in the internet, Learning Management Systems (LMS), and AI technology. The implementation of e-learning in schools and universities shares similarities in the use of technology and accessibility of materials, but differs in the level of student independence and the complexity of the materials. While e-learning offers advantages such as flexibility, cost-efficiency, and access to extensive learning resources, it faces significant challenges such as limited access to technology, lack of social interaction, and the need for high levels of self-discipline. This study analyzes the historical development of e-learning, its implementation at various levels of education, and identifies its strengths and weaknesses as a foundation for more effective and inclusive educational transformation in the future.